PENGARUH BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR (POC) URIN SAPI TERHADAP PERTUMBUHAN SEMAI KAYU PUTIH (Melaleuca leucadendra) - Margaretha Vani Bima; Wilhelmina Seran; Astin E Mau (Wana Lestari, 2020)
Eucalyptus (Melaleuca leucadendra) is the result of a non-timber forest that utilized its leaves to be used as eucalyptus oil (cajaput oil) which will be used as medicine, insecticides and fragrances. The propagation of Eucalyptus is done in order to meet the needs of eucalyptus oil (cajaput oil) in Indonesia. The aim of this research was to determine the appropriate concentration of liquid organic fertilizer of cow urine on the growth of eucalyptus seedlings. This research was conducted at the permanent nursery Fatukoa in January to April 2020. The research method uses Complete Random Design (CRD) with 4 treatments that are A0 (0ml/1000ml), A1 (150ml/1000ml), A2 (250ml/1000ml) and A3 (350ml/1000ml). The parameters of the observation measured are the height of the plant, diameter, leaf number, dry weight and the percentage of life of eucalyptus seedlings. To find out the difference between the treatment it was tested Honestly Significant Difference (HSD). The results showed that application of liquid organic fertilizer cow urine is significantly affected to parameters of plant height, leaf number and dry weight, but is not significant affect to parameters of diameter and percentage of life. The concentration of 150ml/1000ml provides better growth results than other concentrations.